China as the Rising Hegemon: Need for Global Cultural Adjustment? - Savage, Victor Roger (2017)
The global community’s cultural adjustment to China’s rise as a global hegemon will be prolonged and vexatious. Given the long western dominance, the Chinese ‘cultural way’ might be cause of much political tension in East-West relationships.